Women’s Socio-Demographic Characteristics And Their Experience Of Domestic Violence: A Case Study Of Awutu Senya East - Addai, B.K. (University of Ghana, 2016)
Domestic violence is a universal problem found in all societies around the world. Victims feel reluctant to speak of it in public. This is because of the shame and stigmatization associated with it. The focus of this study was to investigate women’s socio-demographic characteristics and their experience of domestic violence using Awutu Senya East District as a case study. The research employed a quantitative approach which administered close ended questionnaire to 120 women above age 18 years selected from the district. Using descriptive statistical analysis, it was found that physical abuse was the commonest form of abuse. The least reported form of domestic abuse among the sample was economic and psychological abuse. Using Multivariate Pearson Correlation analysis with a significance value of 0.05, the study found that respondents’ income, education, relationship status and employment status were not associated with domestic violence. However, age was correlated with domestic violence; older women were less likely to face domestic violence compared to younger women. Some victims felt reluctant to report issues of domestic violence, however the study found that 53 percent of respondents who have experienced abuse said they reported violence meted to them. Out of the abused respondents (12.5 percent), 76.5 percent reported the abuse to their relatives. The study also found that 40 percent of the study respondents opted for education as the best intervention to reduce domestic abuse. The study recommended that the Awutu Senya East District Assembly, National Council for Civic Education (NCCE), and Non-Governmental Organizations intensify their campaign to encourage more women to engage in economic activities, go to school to improve their status in society. This will reduce domestic violence. Public awareness creation that domestic violence is a criminal act and perpetrators are liable to be arrested is also recommended.
Thesis (MA)
Keywords: Socio-Demographic Characteristics; Women; Domestic Violence; Experience; Awutu Senya East; Ghana